A formative evaluation of LPC’s Montessori Preschool Programme - Ubisse, Amosse Francisco (Organisational Psychology, 2020)
Research shows that early childhood interventions with fidelity to Montessori model generate learner’s outcomes that outperform the traditional model. The evidence is confirmed in developed and in developing countries. This formative evaluation reports the results of a Montessori model in implementation in township of Mfuleni, located in Cape Town, South Africa. Providing insights into the functioning of the programme, the evaluation confirms that the roll out of the Montessori model is still underway which may explain the reason of the learners not outperforming the comparison group.